Private corporate sector : generation and regeneration of wealth - Choudhury, Uma Datta Roy.; National Institute of Public Finance and Policy (India) (New Delhi : Vikas Pub. House, 1996)
With reference to India.
"Issued under the auspices of National Institute of Public Finance and Policy."
Includes bibliographical references (p. [196]-202) and index.
Keywords: Corporations -- India -- Finance